LEED practices, certification, and accreditation handbook - Kubba, Sam (Butterworth-Heinemann, 2010)
Adopted in the United States and a number of other countries, LEED? certification is the recognized standard for measuring building sustainability. Achieving LEED? personal certification or project certification is the best way to demonstrate that the project is truly "green." Written by an architect with over 30 years of international experience, this book provides architects, designers, building owners, and construction engineers with an easy to understand guide to the nuts and bolts of LEED? project and personal certification. Written in plain and easy to understand language, this?hands on? book is designed to assist readers with all aspects of LEED? certification. The handbook follows the rigorous third-party commissioning process, beginning with basic LEED? concepts, and then carefully explains LEED? documentation and technical requirements along with its standards, professional accreditation, and codes. The handbook provides readers with design strategies for sustainable site selection, and design process for high performance building and commissioning. Other important topics include green materials and products selection as well as strategies for ensuring Indoor Environmental Quality (IEQ), water efficiency and sanitary waste disposal. This handbook also offers readers a multitude of forms with expert guidance for their completion. Clear and authoritative in scope, LEED? Practices and Accreditation Handbook provides architects, builders/owners, construction managers, and engineers with a reference that will help them to offer their clients, peers, and the public at large compelling proof that they have achieved their projects environmental goals and that the building is performing as designed. Instruction for completing LEED? checklist and forms Detailed explanation of the third-party commissioning process Explains LEED? documentation & technical requirements Topics include green materials and products selection